2023
DOI: 10.1126/sciadv.adg0432
|View full text |Cite
|
Sign up to set email alerts
|

A bending rigidity parameter for stress granule condensates

Abstract: Interfacial tension plays an important role in governing the dynamics of droplet coalescence and determining how condensates interact with and deform lipid membranes and biological filaments. We demonstrate that an interfacial tension-only model is inadequate for describing stress granules in live cells. Harnessing a high-throughput flicker spectroscopy pipeline to analyze the shape fluctuations of tens of thousands of stress granules, we find that the measured fluctuation spectra require an additional contrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 67 publications
1
2
0
Order By: Relevance
“…The resulting 3D data revealed that stress granules form electron-dense regions with irregular shapes (Fig. 1d, e), partially consistent with previous observations using conventional TEM 12,16 . The captured granules were at their late stage, with diameters exceeding one micrometer.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The resulting 3D data revealed that stress granules form electron-dense regions with irregular shapes (Fig. 1d, e), partially consistent with previous observations using conventional TEM 12,16 . The captured granules were at their late stage, with diameters exceeding one micrometer.…”
Section: Resultssupporting
confidence: 90%
“…Given many stress granule components are translation modifiers and their formation coincides with reduced global translation, it is commonly assumed they directly contribute to this repression 11 . However, emerging evidence suggests stress granules may be dispensable for global translation shutdown 4,12 , and translation levels may be comparable both within and outside them 13 . Therefore, understanding the molecular architecture and cellular context of stress granules is essential for a comprehensive understanding of their precise functions.…”
Section: Introductionmentioning
confidence: 99%
“…9,22,27 This energy scale is bordered either side by interfaces in colloid-polymer mixtures (g B 1 mN m À1 ) and complex coacervates (g B 100 mN m À1 ), 28,32 and similar to recent surface tension measurements for native intracellular condensates (0.1-10 mN m À1 ). 58 Condensates formed by Ddx4 N 1-231, with a net charge of À2.1e at pH 8.0, showed a decreased stability and surface tension, by factors of 1.4 and 2.1 respectively, relative to Ddx4 N 1-229 (net charge À1.1e). We and others, 19,59 have previously rationalised the detrimental impact of increased absolute protein charge on condensate stability as a weakening of the mean-field interactions between proteins.…”
Section: Discussionmentioning
confidence: 96%